Physicochemical Studies on Orientation and Conformation of a New Bacteriocin BacSp222 in a Planar Phospholipid Bilayer - Pieta, Piotr (Langmuir : the ACS journal of surfaces and colloids, 2016)
The behavior, secondary structure, and orientation of a recently discovered bacteriocin-like peptide BacSp222 in a lipid model system supported at a gold electrode was investigated by chronocoulometry, polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS), and attenuated total reflectance infrared (ATR-IR) spectroscopy. The IR spectra show that the secondary structure of BacSp222 is predominantly α-helical. Analysis of the spectra in the amide I region shows that the α-helical fragment of the peptide is inserted into bilayer at the potential range at which the bilayer is stable and attached to the Au(111) surface, i.e., from -0.5 to 0.3 V vs Ag/AgCl. Insertion of BacSp222 to the membrane significantly changes the conformation of the acyl chains of lipid molecules, from all-trans to partially melted; however, the chains become less tilted. Based on these results, we propose that BacSp222 interacts with the DMPC bilayer through the barrel-stave pore formation. In this model, α-helix of BacSp222 inserts into the membrane with an angle between the α-helix axis and membrane normal equal to ∼18°. The changes in orientation of the α-helical fragment of the peptide indicate that the orientation of BacSp222 with respect to the bilayer surface is potential-dependent. The peptide is inserted into the membrane driven by the electrostatic field generated by negative charge at the metal surface. It is not inserted at negative potentials where the membrane is detached from the metal and no longer exposed to the electrostatic field of the metal